Web-based Panggung Lestari Village-Owned Enterprises (BUMDES) Integrated Service Information System - Fidiantoro, Vicky; Rianto, Rianto; Putri, Puji Handayani (Compiler, 2024)
Village-Owned Enterprises (BUMDes) are village business institutions whose businesses are run by village communities and the village government to improve village welfare. BUMDes was formed as a business institution that can manage various businesses according to the needs and potential of the village. However, BUMDes face challenges in managing their business, such as recording transactions and reports. This research is to design and implement a website-based BUMDes integrated service information system at BUMDes Panggung Lestari. This system design uses a programming language PHP with framework codeigniter and database MySQL. The system development method used is SDLC (System Development Life Cycle) model waterfall. The web-based BUMDes integrated service information system is very effective and efficient used by BUMDes for managing, monitoring and supervising business activities. This system is designed to include features for recording income transactions or business operational costs, as well as providing reports that can be used for analysis and evaluation of operational performance, and providing information services to the public regarding information about BUMDes.